A Hybrid BTC Based Compression Techniques of General Images - Kamalin, C. Jenifer; MuthuLakshmi, G. (International Journal of Membrane Science and Technology, 2023)
In this paper we propose a new approach for the compression of the general images by combining the Discrete Wavelet Transform (DWT) with Adaptive Block Truncation Coding –Edge Quantization (ABTC- EQ). At the first the standard image is processed by DWT decomposition and into its approximations and details. From this finer and approximation details are separated. The finer details of the image then noted and discarded. The approximate details are noted and further processed in to ABTC-EQ. This approach i.e combination of DWT with AMBTC-EQ gives a better result than other techniques. The Peak Signal to Noise Ratio (PSNR), Weighted Peak Signal to Noise Ratio (WPSNR), Bit Rate (BR), and Structural SIMilarity Index (SSIM) are among the parametric measurements that are used to evaluate image quality. The comparison analysis demonstrates that the suggested algorithm outperforms both BTC and ABTC-EQ.